A Study on Hand Hygiene Compliance among Health Care Professionals in ICU of a Selected Hospital - Maharjan, U; Mathew, S (Journal of Chitwan Medical College, 2013)
Hand Hygiene is one of the best measures to control infection. Through structured questionnaire, the WHO hand hygiene compliance tool and structured teaching programme recommended by the WHO, Pre and post tests were done 1 week after and 1 month after which resulted that adherence to hand hygiene compliance was not satisfactory among Healthcare Professionals. The interventional study through teaching programme was not significantly effective to improve their compliance due to short span of time. To have enduring effect, there is a need of continuous teaching programme on long term basis. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8629 Journal of Chitwan Medical College 2013; 3(3): 4-9